Вплив думки дитини при її поверненні в контексті Гаазької Конвенції Про цивільно-правові аспекти міжнародного викрадення дітей - Стоянова, Тетяна Анатоліївна; Стоянова, Т. А.; Stoianova, Tetiana A. (Херсон : Видавничий дім «Гельветика», 2019)
Нині дуже гостро встає питання про проблеми викрадення дітей. Статистика підтверджує, що таке явище, як викрадення дітей – має вкрай небезпечний характер. За даними Європейської комісії, щорічно в країнах ЄС пропадають 250 тисяч дітей, тобто 1 дитина – кожні 2 хвилини. В Україні відсутні спеціальні юрисдикційні органи, що відповідають за комплексне врегулювання даної проблеми; відсутній механізм підтримки та реабілітації постраждалих сімей та повернутої дитини. Викрадення дітей – це особливе соціальне явище, що знаходиться в площі регулювання декількох галузей права. Стаття присвячена аналізу правового регулювання основних законодавчих актів країн ЄС та України, розгляду проблем практичного застосування Гаагської Конвенції 1980 року, запропоновано поняття «викрадення дітей», розглянуті проблеми судового розгляду справ такої категорії.

There are no special jurisdictional bodies in Ukraine responsible for the comprehensive regulation problem of kidnapping. There is no mechanism for supporting and rehabilitating the affected family and the returned child. The issues of abduction of children should be considered taking into account psychological, social and geopolitical aspects – this will allow not to miss the integrity of the phenomenon and lead to an effective solution to key problems. The abduction of children is a special social phenomenon lying in the plane of several sciences and several branches of law of the entire international community. This issue will be considered not only in the context of jurisprudence, or legislative regulation. It is necessary to solve the problems of abduction of children taking into account psychological, social and geopolitical aspects – this will allow not to miss the integrity of the phenomenon being studied, which willead to the effectiveness of solving key problems. The abduction of children is a separate social phenomenon lying in the plane of several sciences and several branches of law of the entire international community. This article will be written by several hypotheses: The abduction of children is an international problem, a separate institution that requires attention, knowledge and control in several areas: psychological, social, legal. The need to single out a common concept of child abduction and to separate the concept of child abduction in the criminal and civil law aspects at the level of EU legislation, as well as to create a structure for the institution of child abduction, is the way to structure and, therefore, increase the legislative mechanism for protecting children in the world. The need to strengthen cooperation between special bodies authorized to deal with the problems of the return of children, including the creation of special bodies dealing with the problem of the return of children and their psychological rehabilitation after return.
Стоянова Т. А. Вплив думки дитини при її поверненні в контексті Гаазької Конвенції Про цивільно-правові аспекти міжнародного викрадення дітей / Т. А. Стоянова // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Херсон : Видавничий дім «Гельветика», 2019. – Вип. 34. – С. 62-66.
Keywords: цивільний процес; цивільний процесуальний кодекс; викрадення дітей; Гаагська Конвенція; повернення дитини; civil process; civil procedural code; kidnapping, the Hauge Convention; child’s returning; Research Subject Categories::LAW/JURISPRUDENCE